Single dose aspirin affects fecal immunohistochemical test sensitivity in detecting advanced colorectal neoplasms: Truth or expectation? - Yonca Yılmaz Ürün,; Selim Aydemir, (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Yılmaz Ürün Y. Single dose aspirin affects fecal immunohistochemical test sensitivity in detecting advanced colorectal neoplasms: Truth or expectation? Turk J Gastroenterol 2020; 31(1): 80-2.